Majas dalam Novel Buya Hamka Karya Ahmad Fuadi - Nisa, Hikmah Mughni Nur An; Usman, Usman; Hasriani, Hasriani (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2025)
This study aims to describe the form and function of figurative language in the novel Buya Hamka by Ahmad Fuadi. The research method used is descriptive qualitative with data collection techniques through note-taking and observation techniques. The data in this study are sentences containing figurative language in the novel Buya Hamka by Ahmad Fuadi and the data source used is the novel entitled Buya Hamka by Ahmad Fuadi. The results of the study show that the most dominant figurative language is comparison contained in the novel Buya Hamka by Ahmad Fuadi. This figurative language has a function according to the meaning of the sentence, such as creating imagination, showing emotions, figurative meaning, adding aesthetics, encouraging critical thinking, and emphasizing meaning.